HIV Screening of Patients Presenting for Routine Medical Care in a Primary Care Setting - Mamle Anim; Ronald J. Markert; Nkeiruka E. Okoye; Wissam Sabbagh (SAGE Publishing, 2013)
Background: HIV screening is recommended for all patients between the ages of 13 and 64 years. Objective: To increase the rate of HIV screening in a primary care setting by routinely offering HIV screening to all patients. Methods: All patients seen over a 3-month period in the authors' clinic were offered HIV screening by a medical assistant. Results: During the 3-month study period, 17% of patients offered HIV testing accepted screening, a large increase from the less than 1% rate of an earlier time period. Conclusion: HIV screening can be increased by routinely offering the test to all patients in the office. Use of trained health care professionals other than physicians may increase the number of patients screened.